Debonding forces of different pads in a lingual bracket system - Arima,Valter O. (2017)
ABSTRACT Objective: To evaluate the shear bond strength of lingual orthodontic brackets with resin or metal pads, the location of bond failure and the adhesive remnant index (ARI). Methods: A total of 40 extracted upper premolars were randomly divided into two groups of 20 each: bonding with brackets having (1) pads with extended resin directly on the lingual surface of teeth, and (2) pads with metal custom base on the lingual surface of teeth. The debonding force was measured with an Instron universal testing machine. A Student’s t-test was used to assess the difference between groups (α = 0.05). Results: The results showed a significant difference between the groups (p < 0.001). The shear bond strength of metal pads was significantly higher than resin pads. Conclusions: Within the limitations of this in vitro study, it was concluded that the bond strength of lingual brackets with metal pads was higher than that of brackets with composite resin pads, due to the metal part being a single unit and welded. The failure location in the region between the bracket and the resin pad affected a higher percentage of the resin pads than the metal pads.